2017
DOI: 10.2196/mhealth.7798
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging and Mobile Phone Apps as Interventions to Improve Adherence in Adolescents With Chronic Health Conditions: A Systematic Review

Abstract: BackgroundThe number of adolescents with chronic health conditions (CHCs) continues to increase. Medication nonadherence is a global challenge among adolescents across chronic conditions and is associated with poor health outcomes. While there has been growing interest in the use of mHealth technology to improve medication adherence among adolescents with CHCs, particularly text messaging and mobile phone apps, there has been no prior systematic review of their efficacy.ObjectiveThe purpose of this review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
140
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(154 citation statements)
references
References 51 publications
(167 reference statements)
12
140
0
2
Order By: Relevance
“…Finally, Pain Squad was the only app with evidence in the literature to support its use, indicating continued gaps in knowledge when it comes to correlating app use to clinical efficacy. Again, this is consistent with other reviews examining technology interventions designed to improve medication adherence …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Pain Squad was the only app with evidence in the literature to support its use, indicating continued gaps in knowledge when it comes to correlating app use to clinical efficacy. Again, this is consistent with other reviews examining technology interventions designed to improve medication adherence …”
Section: Discussionmentioning
confidence: 99%
“…Currently, access to mHealth is becoming ubiquitous, with 73% of adolescents having access to personal technology, such as smartphones . In recent years, interest in the use of technologies to improve both medication adherence and self‐management of disease has also grown . A systematic review of healthcare interventions delivered by cell phones with basic features reported improvements in outcomes including, medication adherence .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the ubiquity of mobile phones among adolescents, it can be efficiently and effectively used as a means to deliver interventions to this population (Badawy et al, ; Majeed‐Ariss et al, ). Using mobile phones requires fewer efforts and costs compared with traditional face‐to‐face interventions with health professionals (Abraham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Improve medication adherence [43]and 2. Improve preventative behavior [44] in teens with chronic disease.…”
Section: Discussionmentioning
confidence: 99%